"It's Catchy, but It Gets You F*cking Nowhere": What Viewers of Current Affairs Experience as Captivating Political Information. (April 2017) - Groot Kormelink, Tim; Costera Meijer, Irene
This paper explores how political information can be told in such a way that news users experience it as captivating. More specifically, it seeks to move beyond Irene Costera Meijer's "double viewing paradox" and bridge the gap between what attracts and satisfies viewers by developing bottom–up, user-defined, quality criteria for current affairs TV. Items from two Dutch current affairs shows were watched and discussed with fifty-four viewers. A key finding is that participants greatly appreciated feeling enabled to better understand how politics work and impact society. This suggests that what viewers want from political journalism might differ from what journalists produce yet is perfectly compatible with their democratic remit.